2017
DOI: 10.1186/s12879-017-2749-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of larval source management and house improvement on malaria transmission when added to standard malaria control strategies in southern Malawi: study protocol for a cluster-randomised controlled trial

Abstract: BackgroundDue to outdoor and residual transmission and insecticide resistance, long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS) will be insufficient as stand-alone malaria vector control interventions in many settings as programmes shift toward malaria elimination. Combining additional vector control interventions as part of an integrated strategy would potentially overcome these challenges. Larval source management (LSM) and structural house improvements (HI) are appealing as addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
87
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(90 citation statements)
references
References 82 publications
0
87
0
1
Order By: Relevance
“…Therefore, aquatic habitats are important for mosquito breeding. Larval source management (LSM) involves the management of water bodies that are potential larval habitats to prevent the development of immature mosquitoes into adults [18,19], and studies have shown that mosquito LSM has an important potential impact on mosquito-borne disease transmission both in urban and rural areas [20][21][22]. For example, in urban areas of Dar es Salaam, Tanzania, the use of larvicides reduced the risk of malaria infection in 5-year-old children [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, aquatic habitats are important for mosquito breeding. Larval source management (LSM) involves the management of water bodies that are potential larval habitats to prevent the development of immature mosquitoes into adults [18,19], and studies have shown that mosquito LSM has an important potential impact on mosquito-borne disease transmission both in urban and rural areas [20][21][22]. For example, in urban areas of Dar es Salaam, Tanzania, the use of larvicides reduced the risk of malaria infection in 5-year-old children [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the rural highlands of western Kenya, a combination of larvicides and insecticide-treated bed nets (ITNs) decreased new malaria infections by a factor of two compared to ITNs alone [24]. Accordingly, LSM should be considered a crucial part of any integrated mosquito management programme as a complementary means of controlling the spread of mosquito-borne diseases [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…The current analysis is based on the Majete Malaria Project (MMP), in Chikwawa District in Southern Malawi [19]. MMP is a multi-stakeholder community-based project for malaria control.…”
Section: Introductionmentioning
confidence: 99%
“…MMP is a multi-stakeholder community-based project for malaria control. Embedded within its community-based activities is an RCT testing malaria intervention in various combinations [19]. The context of this research in presented in the protocol publication by McCann et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our literature search in Web of Science on spatial sampling of mosquitoes (search terms: mosquito or anopheles AND sampling AND spatial, in title/keywords/abstract) shows that while all studies provide a general description of the sampling design, only a limited number of papers (i.e. (8)(9)(10)(11)) give a detailed description of the rationale, decisions and calculations related to the "Where, When, How and How many" samples to collect (see for example the reviews from (12) and (13)). In other literature, partial justification of the sampling design is provided.…”
Section: Introductionmentioning
confidence: 99%